Pendidikan Kesehatan Bahaya Minuman Beralkohol pada Masyarakat - Suat, Hatty; Haulussy, Rais; Rieuwpassa, Sarmalina; Lalihun, Ishaka; Suat, Rahmawati; Sallo, Andi Kamal M. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Enforcement of Ambon City Regional Regulation number 2 of 2015 concerning the control and supervision of alcoholic beverages. The purpose of PkM is through Health education to increase the knowledge of residents and to avoid and stop consuming alcoholic beverages. The method used is to conduct counseling by gathering residents and entering most of the residents' homes to provide a basic understanding of the negative impacts of alcoholic beverages on health. In this activity, the discussion method is used. The results that in the process of health education on the dangers of alcoholic beverages, the participants were very active in participating in the activity can be seen from several questions asked both from residents and from young people who feel very uneasy with their residential environment. The community service activities carried out can be concluded that this PkM activity can provide knowledge for teenagers about the impacts of consuming alcoholic beverages and provide understanding for the community, especially in supervising the association of children and the community itself in the social environment.